Vitamins vs. Antivitamins: Unmasking the Metabolism of Vitamin B₆ by Positron Emission Tomography for Detection of Lung Cancer - Torrens, Aidan (Université d'Ottawa | University of Ottawa, 2024)
Drug resistance is a major challenge leading to low survival amongst diseases like lung cancer, the most diagnosed cancer in Canadians. Cisplatin is the current standard of care, but resistance is common after 4-6 months. A strong association between treatment outcomes and the metabolism of Vitamin B₆, or Pyridoxine (PN), has been found, where the active form of PN is associated with effective chemotherapy, while the inactive metabolite is associated with resistance. Previous work using contrast agents by MRI have begun addressing this need, but clinical relevance is limited due to motion of the lungs and perturbance of metabolic processes. Herein we focused on developing a non-invasive way to detect the onset of cancer resistance from Cisplatin-based chemotherapy using Positron Emission Tomography (PET). Towards this goal, three cold analogues of PN were prepared, with successful fluorine and carbon substitutions. Metabolomic analysis found interaction with pyridoxal kinase, phosphatase, and oxidase enzymes, showing cell transport and metabolic transformations were maintained. This was followed by radiolabelling efforts, where fluorination was unsuccessful due to low [¹⁸F]HF concentrations. However, carbon radiolabelling showed apparent product formation, with work currently being done to optimize reaction conditions, purification, and characterization. With optimized radiotracers in-hand, future work will focus on differentiating chemotherapy responsive and resistant lung cancer by PET imaging in animal model tumour tissue. PET imaging is performed routinely in clinic, and the rapid translation of radiotracers to clinical use (18 months) suits the need for rapid response to this clinical challenge, improving patient treatment outcomes.
Keywords: PET; Radiotracer; Vitamin B6